Synthesis and physical-chemical properties of 2-(5-(1Н-tetrazol-1-ylmethyl)-4-R-4Н-1,2,4-triazol-3-yltio)-acetic (propanoic), 2-, 4-(5-(1Н-tetrazol-1- ylmethyl)-4-phenyl-4Н-1,2,4-triazol-3- yltiometil)-benzoic acids and their salts - Y. S. Hulina; A. G. Kaplaushenko (Zaporozhye State Medical University, 2016)
Scientists around the world pay considerable interest to chemistry of 1,2,4-triazole and 1,2,3,4-tetrazole thanks to the number of valuable properties of this class of compounds. Literary sources indicate that the core of 1,2,4-triazol and 1,2,3,4-tetrazol are fragments of many known drugs and bioactive compounds. Therefore, synthesis, studying physical, chemical and biological properties of the salts and acids that contain 1,2,4-triazole and 1,2,3,4-tetrazole is relevant both from a theoretical and practical perspective. Purpose - the synthesis of new low-toxic and highly efficient compounds among 5-(1H-tetrazol-1-ylmethyl)-4-R-4H-1,2,4-triazol-3-thiol derivatives, and the establishment of physical-chemical properties of all synthesized compounds. Materials and methods. As starting materials for synthesis of 2-(5-(1Н-tetrazol-1-ylmethyl)-4-R-4Н-1,2,4-triazol-3-yltio)-acetic (propanoic), 2-, 4-(5-(1Н-tetrazol-1- ylmethyl)-4-phenyl-4Н-1,2,4-triazol-3- yltiometil)-benzoic acids we used 2-(5-(1Н-tetrazol-1-ylmethyl)-4-R-4Н-1,2,4-triazol-3-yltio)nitrils. 2-(5-(1Н-tetrazol-1-ylmethyl)-4-R-4Н-1,2,4-triazol-3-yltio)-acetic (propanoic), 2-, 4-(5-(1Н-tetrazol-1- ylmethyl)-4-phenyl-4Н-1,2,4-triazol-3- yltiometil)-benzoic acids have been obtained by two ways: acid and alkaline hydrolysis. For the analysis synthesized compounds have been purified by crystallization from ethanol. Salts of 2-(5-(1Н-tetrazol-1-ylmethyl)-4-phenyl-4Н-1,2,4-triazol-3-yltio)-acetic and 2-, 4-(5-(1Н-tetrazol-1- ylmethyl)-4-phenyl-4Н-1,2,4-triazol-3- yltiometil)-benzoic acids have been synthesized from aforementioned acids by their interaction with salts of the Zn2+, Fe2+, Cu2+, K+ and Na+ in an alkaline medium. Organic salts have been obtained with methylamine (diethylamine) in alcohol medium followed by evaporation of the solvent. The synthesized compounds have been crystallized using mixture ethanol:water 1: 1. Results. Two synthesis methods of 2-(5-(1Н-tetrazol-1-ylmethyl)-4-R-4Н-1,2,4-triazol-3-yltio)-acetic (propanoic) and 2-, 4-(5-(1Н-tetrazol-1- ylmethyl)-4-phenyl-4Н-1,2,4-triazol-3- yltiometil)-benzoic acids have been roposed, one of the methods has been recommended as preparative. Also salts of 2-(5-(1Н-tetrazol-1-ylmethyl)-4-phenyl-4Н-1,2,4-triazol-3-yltio)-acetic and 2-, 4-(5-(1Н-tetrazol-1- ylmethyl)-4-phenyl-4Н-1,2,4-triazol-3- yltiometil)-benzoic acids have been synthesized. Conclusions. While synthetic studies 14 new, indescribable earlier compounds have been obtained. The structure and individuality of all synthesized compounds has been confirmed by complex of physical and chemical methods of analysis.